Hyaluronic Acid as a New Biomarker to Differentiate Acute Kidney Injury From Chronic Kidney Disease (Iranian Journal of Kidney Diseases, 2017)
Introduction. It may be difficult to differentiate acute kidney injury from chronic kidney disease in patients with no past medical reports of kidney function. This study aimed to investigate the role of serum hyaluronic acid (HA), which is known as a marker of fibrosis, in differential diagnosis of kidney failure. Materials and Methods. A total of 90 patients (52 women and 38 mne) admitted to our renal unit with uremia for the first time were included. Serum HA level was measured. The diagnostic role of the test was investigated using the receiver operator curve curves. Results. The mean age of the patients was 54.6 ±17.9 years. The diagnosis was chronic kidney disease (CKD) in 41.1%, acute kidney injury (AKI) in 48.9%, AKI on CKD in 6.7% (3 died without a diagnosis). The mean serum HA was significantly higher in the CKD group (146.1 ± 119.3 ng/mL) than the AKI group (68.9 ± 69.1 ng/mL; P < .001). Serum HA significantly correlated with proteinuria (r = 0.717, P < .001) and serum albumin level (r = - 0.599, P < .001) in the CKD group only. Serum HA cutoff level of 61 ng/dL had a sensitivity of 82% and specificity of 67% for differential diagnosis of AKI and CKD. Conclusions. Serum HA level may be used as tool to differentiate AKI from CKD. Further larger studies are warranted to clarify the definite the role of this marker.